1996
DOI: 10.1097/00005373-199611000-00020
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Patient Outcomes Comparing Trauma Team Activated Versus Trauma Team not Activated Using TRISS Analysis

Abstract: In a Level I trauma center, the outcomes of trauma patients with an ISS > 12 are statistically significantly better if the trauma team is activated than if the patients are managed on an individual service-by-service basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
10

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 18 publications
0
54
0
10
Order By: Relevance
“…In previous studies, it has been suggested that a high percentage of falls in an older cohort may bias the results, because this patient population likely has more comorbid illness, resulting in a worse than predicted outcome. 6 TRISS analyses are unable to control for this. When we excluded falls from the analyses, the AMT group still had significantly better survival than predicted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been suggested that a high percentage of falls in an older cohort may bias the results, because this patient population likely has more comorbid illness, resulting in a worse than predicted outcome. 6 TRISS analyses are unable to control for this. When we excluded falls from the analyses, the AMT group still had significantly better survival than predicted.…”
Section: Discussionmentioning
confidence: 99%
“…From this, we are provided with a Z statistic and a W score. 6 The Z statistic compares the sample population mortality to that of an established database of trauma outcomes. A Z statistic < -1.96 indicates that the sample population did worse than predicted.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 A team approach results in more rapid resuscitation and stabilisation of the patient and reduces the time between injury and critical interventions. The leader of the trauma team is often a qualified surgeon or emergency physician who coordinates the resuscitation efforts and ensures adherence to ATLS guidelines.…”
mentioning
confidence: 99%
“…Comprehensive trauma networks, based on identification of Major Trauma Centers (MTCs) and secondary acute care hospital into a hub and spoke model, together with integrated prehospital care systems, are associated with improved outcomes [1,2]. Helicopter Emergency Medical System (HEMS) is internationally involved in trauma regional organization, with specific training of HEMS crews, according to the constitution of MTCs in-hospital Trauma Teams [3][4][5]. Trauma System in Emilia-Romagna region (Italy) is based on 3 Integrated Trauma Systems called SIAT with MTC each.…”
Section: Introductionmentioning
confidence: 99%